The 'error room': an innovative approach to safety education for midwives in Morocco. - Mochhoury, Latifa; goundali, Khaddouj El; Masnaoui, Lalla Asmaa Katir; Msatfa, Nabila; Chebabe, Milouda (British Journal of Midwifery, 2026)
Background/Aims: The error room is a simulation designed to develop situational awareness and hazard recognition. This study aimed to evaluate students' performance during a maternity-focused error room simulation in Morocco. Methods: A descriptive comparative study was conducted at the Moroccan Institute for Higher Health Sciences. A maternity error room scenario was implemented, incorporating 27 predefined errors and hazards. A total of 51 final-year student midwives participated in individual and team-based sessions, during which they identified as many errors as possible. Individual and team results were compared using the Wilcoxon signed-rank test. Results: Visible environmental- and infection-related errors were more frequently identified, while emergency- and medication-related hazards were less commonly recognised in individual assessment. Team participation significantly improved overall error detection (P<0.001). Participant feedback was highly positive, with 98% reporting satisfaction with the experience. Conclusions: The error room is an effective educational tool for enhancing safety awareness among student midwives. Team participation significantly improves hazard recognition and supports development of situational awareness and teamwork skills essential for safe maternity care. Implications for practice: Integrating error room simulations into midwifery education may strengthen safety culture and preparedness for obstetric emergencies.